2021
DOI: 10.1371/journal.pbio.3001142
|View full text |Cite
|
Sign up to set email alerts
|

Sustained neural rhythms reveal endogenous oscillations supporting speech perception

Abstract: Rhythmic sensory or electrical stimulation will produce rhythmic brain responses. These rhythmic responses are often interpreted as endogenous neural oscillations aligned (or “entrained”) to the stimulus rhythm. However, stimulus-aligned brain responses can also be explained as a sequence of evoked responses, which only appear regular due to the rhythmicity of the stimulus, without necessarily involving underlying neural oscillations. To distinguish evoked responses from true oscillatory activity, we tested wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 90 publications
5
80
1
Order By: Relevance
“…Finally, three recent studies have found evidence for persistent entrainment in the auditory domain, in response to isochronous sequences of tones (Pesnot Lerousseau et al, 2021;Wilsch, Mercier, Obleser, Schroeder, & Haegens, 2020) and isochronously presented speech (van Bree, Sohoglu, Davis, & Zoefel, 2021). However, in the first two cases, persistent entrainment was not specific to the frequency of the input (Wilsch et al, 2020), or only occurred in the gamma range, but not the delta range, which is of importance for temporal expectations (Pesnot Lerousseau et al, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…Finally, three recent studies have found evidence for persistent entrainment in the auditory domain, in response to isochronous sequences of tones (Pesnot Lerousseau et al, 2021;Wilsch, Mercier, Obleser, Schroeder, & Haegens, 2020) and isochronously presented speech (van Bree, Sohoglu, Davis, & Zoefel, 2021). However, in the first two cases, persistent entrainment was not specific to the frequency of the input (Wilsch et al, 2020), or only occurred in the gamma range, but not the delta range, which is of importance for temporal expectations (Pesnot Lerousseau et al, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…However, unlike the well-documented immediate (online) effects of tES, there is less agreement regarding the magnitude and duration of post-stimulus (offline) effects (for review see, Veniero et al, 2015 ). These offline effects cannot be fully explained by a direct continuation of online entrainment (referred to as entrainment “echoes”), since these “echoes” only persist for a few oscillatory cycles following cessation of stimulation ( Marshall et al, 2006 ; Thut et al, 2011 ; Hanslmayr et al, 2014 ; van Bree et al, 2021 ). Therefore, longer-lasting offline effects (referred to as aftereffects) lasting up to 70 min are likely to reflect mechanisms other than entrainment per se (e.g., synaptic plasticity) ( Neuling et al, 2013 ; Veniero et al, 2015 ; Vossen et al, 2015 ; Kasten et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For visualizing the mean frequency response per musical feature, the coherence values at each stimulation tempo were normalized by dividing by the mean coherence across all other stimulation tempi per frequency bin (Fig. 2E-H) (van Bree et al, 2021). As strong coherence was found at the stimulation tempo and the first harmonic, the SRCoh values of each frequency vector were compared between musical features.…”
Section: Eeg -Reliable Component Analysismentioning
confidence: 99%